LOS ESTUDIOS DE CALIDAD DE VIDA: ALTERNATIVA DE EDUCACIÓN BASADA EN LA INVESTIGACIÓN - Jessup C, Margie N; Pulido de Castellanos, Rosalba (Tecné, Episteme y Didaxis: TED, 1998)
This paper presents some reflections based on both the educational practice and the research experience. Developed by a research group, that seeks to generate conceptual discussion and new educational alternatives focused on life quality studies, it pretends to go further in the analysis to prospect integral formation. It is expected that this approach would lead to adequate: curricula, of projects teaching improvement programs and community participation on the school and plans and programs that take would take into account the life quality conditions of the community to generate formative integral processes and a participate solution to a problems. It presents a conceptual evolution about life quality as well as concepts of life level, wellbeing and the weII-being state. Definitions of life quality and human needs are presented which are of critical importance for the research projects, to determinate contextual conditions of the community as a base to educational action research and educational practices in the formal and non formal fields. An application possibility is shown.